Hadal Biodiversity, Habitats and Potential Chemosynthesis in the Java Trench, Eastern Indian Ocean - Jamieson, Alan J.; Stewart, Heather A.; Weston, Johanna N. J.; Lahey, Patrick; Vescovo, Victor L. (Frontiers in Marine Science, 2022)
The Java Trench is the only subduction trench in the Indian Ocean that extends to the hadal zone (> 6000 m water depth), and except for sevenbenthic trawls acquired around the 1950s, there has been little to no sampling at hadal depths undertaken since. In 2019, we undertook a 5-day expedition comprising a scientific dive using a full ocean depth-rated submersible, the DSV Limiting Factor, seven hadal-lander deployments, and high-resolution bathymetric survey. The submersible performed a video transect from the deepest point of the trench, up a 150 m high near-vertical escarpment located on the forearc, and then across a plateau at a depth of ~7050 m to make in situ observations of the habitat heterogeneity and biodiversity inhabiting these hadal depths. We found the Java Trench hadal community to be diverse and represented by ten phyla, 21 classes, 34 orders and 55 families, with many new records and extensions in either depth or geographic range, including a rare encounter of a hadal ascidian. The submersible transect revealed six habitats spanning the terrain. The deepest trench axis comprised fine-grained sediments dominated by holothurians, whereas evidence of active rock slope failure and associated talus deposits were prevalent in near-vertical and vertical sections of the escarpment. Sediment pockets and sediment pouring down the steep wall in ‘chutes’ were commonly observed. The slope terrain was dominated by two species in the order Actiniaria and an asteroid, as well as 36 instances of orange, yellow, and white bacterial mats, likely exploiting discontinuities in the exposed bedrock, that may indicate a prevalence of chemosynthetic input into this hadal ecosystem. Near the top of the escarpment was an overhang populated by >100 hexactinellid (glass) sponges. The substrate of the plateau returned to fine-grained sediment, but with a decreased density and diversity of epifauna relative to the trench floor. By providing the first visual insights of the hadal habitats and fauna of the Java Trench, this study highlights how the habitat heterogeneity influences patchy species distributions, and the great benefit of using a hadal-rated exploratory vehicle to comprehensively assess the biodiversity of hadal ecosystems.